Young children's civic mindedness democratic living and learning in an unequal world - James, Jennifer Hauver (Routledge, 2019)
"Young Children's Civic Mindedness provides a well-grounded understanding of children's civic thought and action by inviting readers to look and listen carefully to the voices of young children themselves. Grounded in research on children's evolving civic identities and drawn from extended case studies and rich narrative vignettes, this book shows the many ways even the youngest children can be civic-minded and political. The book engages readers in thinking about the many ways children reason about and approach civic problems; how children's experience in various local and larger contexts shapes their thinking and action; and the environmental factors that delimit what children see as possible in civic spaces. Written for early childhood, elementary and civic educators, this book encourages readers to go beyond mere rhetoric on the importance of civic education, to develop improved ways of teaching for children's civic development"--Provided by publisher.